2020
DOI: 10.1097/nnd.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Standardized Patient Simulation on Behavioral Health Nurse Resident Confidence and Satisfaction in Learning

Abstract: The transition from student nurse to nurse graduate can be overwhelming. Although nurse residency programs ease this transition, standardized patient (SP) simulations supplementing these programs are underutilized. An SP simulation series was created and imbedded into a behavioral health nurse residency program. Nurse residents were satisfied with the learning experience and gained self-confidence, which was sustained over 30 days. Staff development educators should consider supplementing a nurse residency pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In this study, the degree of satisfaction and self-confidence obtained by nursing students after the high-fidelity clinical simulation was evaluated. The results have shown average scores above 4 for both dimensions, which shows that students satisfactorily value simulation during academic training, these results are similar to those found in other studies that also use the SCLS to assess satisfaction and self-confidence [11,12,18,19,59]. In our sociocultural context, a study also showed that satisfaction with simulation is very high (96% totally agree/In agreement) and that simulation promotes self-confidence (80,6% totally agree/In agreement) [34].…”
Section: Plos Onesupporting
confidence: 87%
“…In this study, the degree of satisfaction and self-confidence obtained by nursing students after the high-fidelity clinical simulation was evaluated. The results have shown average scores above 4 for both dimensions, which shows that students satisfactorily value simulation during academic training, these results are similar to those found in other studies that also use the SCLS to assess satisfaction and self-confidence [11,12,18,19,59]. In our sociocultural context, a study also showed that satisfaction with simulation is very high (96% totally agree/In agreement) and that simulation promotes self-confidence (80,6% totally agree/In agreement) [34].…”
Section: Plos Onesupporting
confidence: 87%
“…Other quasi-experimental design studies in the field of emergency medicine found significant and favourable relationships in the dimensions of satisfaction, confidence, and motivation following the performance of high-fidelity simulations by students [ 23 , 24 ]. Therefore, the benefits of high-fidelity simulations in terms of student learning calls for further research in this field [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation is an instructional strategy that provides for a realistic, safe, and context-rich learning environment to practice clinical skills (National League for Nurses, 2019). Although the kinetic learning of most clinical skills is appropriately simulated with a mannequin, the relationship and communication skills of behavioral health nursing, such as nonverbal cues, body language, facial expression, and physical movements, are not (Haskell & Thul, 2020). Best practices in the simulation course design included performing a needs assessment, developing measurable objectives, designing a realistic scenario, maintaining a participant-centered approach, allotting time for both prebrief and debrief, evaluating learner’s experiences, and providing supplemental materials to assist the learner in meeting the identified learning objectives (INACSL Standards Committee, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%